IEEE 802.11N NETWORK STANDARD CAPACITY EXPERIMENTAL RESEARCH - Одарченко, Р. С.; Ткаліч, О. П.; Полігенько, О. О. (Science-based technologies, 2014)
In the paper the details of the pilot study to test the method proposed by the authors estimate the effective bandwidth of antenna systems MІMO configurations ( 2xM ) and (Nx2), which allows to determine the bandwidth, depending on the desired signal / noise ratio at the receiver input , the probability of occurrence bit errors , the communication range and the number and nature of the obstacles in the path of the radio signal , the meteorological conditions , transmitter power , frequency, radio , the type of terrain.